PERENCANAAN KEUANGAN SYARIAH TERHADAP MINAT MASYARAKAT DALAM MENEMPATKAN DANA DI LEMBAGA KEUANGAN SYARIAH - Wicaksono, Tri; Rafidah, Rafidah; Hamzah, M. Maulana (Universitas Sahid, 2023)
The aim of this research is to find out how financial planning for income and expenses influences people's interest in placing funds in sharia financial institutions. The population used was the Simpang Rantau Gedang community on the grounds that the village was productive and understanding, financial planning with a sample size of 100 people from the Simpang Rantau Gedang community was carried out using non-probability sampling techniques. The method used is a quantitative approach, with this type of research being primary data taken directly through distributing questionnaires and secondary data in the form of data from the Simpang Rantau Gedang Village community as well as searches from the internet and literature. and analysis using multiple linear regression analysis using SPSS software. The results of multiple regression analysis stated that it was 22% and there are still many variables that influence people's interest such as promotion, location, religion.